2006
DOI: 10.1128/aem.00439-06
|View full text |Cite
|
Sign up to set email alerts
|

Abundance of narG , nirS , nirK , and nosZ Genes of Denitrifying Bacteria during Primary Successions of a Glacier Foreland

Abstract: Quantitative PCR of denitrification genes encoding the nitrate, nitrite, and nitrous oxide reductases was used to study denitrifiers across a glacier foreland. Environmental samples collected at different distances from a receding glacier contained amounts of 16S rRNA target molecules ranging from 4.9 ؋ 10 5 to 8.9 ؋ 10 5 copies per nanogram of DNA but smaller amounts of narG, nirK, and nosZ target molecules. Thus, numbers of narG, nirK, nirS, and nosZ copies per nanogram of DNA ranged from 2.1 ؋ 10 3 to 2.6 ؋… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
221
6
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 543 publications
(256 citation statements)
references
References 31 publications
(57 reference statements)
28
221
6
1
Order By: Relevance
“…The abundance of nosZ gene was the highest one among the three functional genes in this study. This result was higher than those of previously reported: nosZ density of 3×10 6 -2.8×10 8 copies g −1 dry soil (Kandeler et al 2006;Dandie et al 2008;Hallin et al 2009). But Chronakova et al (2009) found the nosZ gene copy number was in a range of 9.1×10 7 -7.5×10 9 copies g −1 soil in an upland pasture soil.…”
Section: Abundances Of Nirs Nirk and Nosz Genes Under Different Irrcontrasting
confidence: 73%
See 1 more Smart Citation
“…The abundance of nosZ gene was the highest one among the three functional genes in this study. This result was higher than those of previously reported: nosZ density of 3×10 6 -2.8×10 8 copies g −1 dry soil (Kandeler et al 2006;Dandie et al 2008;Hallin et al 2009). But Chronakova et al (2009) found the nosZ gene copy number was in a range of 9.1×10 7 -7.5×10 9 copies g −1 soil in an upland pasture soil.…”
Section: Abundances Of Nirs Nirk and Nosz Genes Under Different Irrcontrasting
confidence: 73%
“…Environmental factors affected the abundance of the bacterial denitrification genes greatly (Kandeler et al 2006;Yoshida et al 2009). Significantly positive correlations between the soil NO 3 − and the quantity of nirK gene (R=0.682, P<0.05), and between the soil organic matter content and the quantity of nirS gene (R=0.614, P<0.05), were found in this study.…”
Section: Abundances Of Nirs Nirk and Nosz Genes Under Different Irrmentioning
confidence: 99%
“…Pyrosequencing and quantitative kinetic real-time PCR of denitrification-associated genes substantiated the previous conclusion (Figure 4, Tables 4 and 5). narG copy numbers of cryoturbated peat soil were higher than or in the same range as in agricultural soils or glacier forelands Kandeler et al, 2006;Bru et al, 2007), and significantly higher than in unturbated peat soil (Table 5). Such findings are in agreement with the high in situ concentrations of nitrate in cryoturbated peat soil (Repo et al, 2009), and the inability of unturbated peat soil to cope with high nitrate concentrations (Figure 2).…”
Section: Discussionmentioning
confidence: 97%
“…Gene abundances were likewise corrected for gene copy per organism: 1 copy per organism for nifH, nirK, nirS, and nosZ (Hall et al, 2008;Kandeler et al, 2006); 2 copies per organism for amoA (Chain et al, 2003); and 3.6 copies per organism for the 16S rRNA gene (Klappenbach et al, 2001). Relative abundances (from non-log transformed qPCR values) were calculated for each sample as a ratio of the abundance of each N-cycling gene to 16S rRNA gene abundance.…”
Section: Statisticsmentioning
confidence: 99%